The economic impact of the closure of Bong Suwung localization in Yogyakarta City - Mujiyanto, Mujiyanto; Sugiyanto, Sugiyanto (PHINISI, 2025)
The closure of the Bong Suwung localization in Yogyakarta City has proven to have a significant economic impact on the lives of the surrounding community who have been dependent on the economic ecosystem formed in the area. Many informal economic actors such as street vendors, parking attendants, stall owners, and other service providers have lost their main livelihoods. This impact not only leads to a direct decline in income, but also triggers a chain effect in the form of hidden unemployment, forced job transfers, and increased household economic vulnerability. In addition, the closure of this localization also resulted in the cessation of informal economic activities that were previously the backbone of the region's micro-economy. Communities' dependence on the existence of localization makes them particularly vulnerable when these key economic sources are abruptly shut down without adequate transition mechanisms or empowerment. Based on the results of field findings and strengthened by previous studies, it can be concluded that the policy of closing the Bong Suwung localization, if not accompanied by a structured economic assistance and empowerment strategy, has the potential to worsen the economic conditions of the affected residents and create new social inequality. Therefore, further policy interventions are urgently needed to restore and rebuild the economic resilience of communities post-localization closures.